The hemodynamic stability of remimazolam compared with propofol in patients undergoing endoscopic submucosal dissection: A randomized trial - Qiu, Yuwei; Gu, Wei; Zhao, Mingye; Zhang, Yunyun; Wu, Jingxiang (Frontiers in Medicine, 2022)
Objective: Hypotension is common in propofol anaesthesia. Whether remimazolam could reduce intraoperative hypotension remains unknown. We therefore tested the primary hypothesis that remimazolam reduces the incidence of intraoperative hypotension compared to propofol in adult patients undergoing endoscopic submucosal dissection (ESD) surgery. Methods: We conducted a prospective trial to compare patients who received either remimazolam or propofol bolus induction and thereafter intravenous infusion. The haemodynamic parameters were measured using CNAP® Monitor 500 system. Our primary analysis was to compare the incidence of hypotension defined as systolic blood pressure below 90 mmHg between remimazolam and propofol during the whole anaesthesia period. Results: The incidence of hypotension was decreased by 50%, from 67.9% in propofol group to 32.1% in remimazolam group (P<0.01). Patients in remimazolam group received less phenylephrine than propofol group (0 [0-40] μg in remimazolam vs 80[0-200] μg in propofol(P<0.01)). Time-weighted average and cumulative time of hypotension was lower in remimazolam group compared with propofol (P<0.05). Cardiac output continuously measured by CNAP was preserved much better in remimazolam group compared to propofol group(P=0.01), while systemic vascular resistance didn’t differ between groups. The median time from discontinuation of remimazolam until full alertness was 4[3-11.8] min compared to 15[12.0-19.8] min in propofol group(P<0.01). Conclusions: Remimazolam has better hemodynamic stability than propofol in adult patients undergoing ESD surgery. The benefits of remimazolam on hemodynamic stability and hypotension prevention, may be partly contributed to its better preservation of cardiac output.